2008
DOI: 10.1152/ajpregu.00060.2008
|View full text |Cite
|
Sign up to set email alerts
|

Mercaptoacetate inhibition of fatty acid β-oxidation attenuates the oral acceptance of fat in BALB/c mice

Abstract: We investigated the effect of beta-oxidation inhibition on the fat ingestive behavior of BALB/c mice. Intraperitoneal administration to mice of mercaptoacetate, an inhibitor of fatty acid oxidation, significantly suppressed intake of corn oil but not intake of sucrose solution or laboratory chow. To further examine the effect of mercaptoacetate on the acceptability of corn oil in the oral cavity, we examined short-term licking behavior. Mercaptoacetate significantly and specifically decreased the number of lic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 49 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…27) In addition, we have reported that fat metabolism inhibitors suppress the palatability of fat, while a fat or carbohydrate metabolism inhibitor does not affect the palatability of sucrose. 29,30) These observations suggest that the mechanisms for the palatability of sucrose and fat differ. In this study, administration of opioid receptor antagonists strongly suppressed the preference for Intralipid compared to sucrose in the two-bottle choice test (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…27) In addition, we have reported that fat metabolism inhibitors suppress the palatability of fat, while a fat or carbohydrate metabolism inhibitor does not affect the palatability of sucrose. 29,30) These observations suggest that the mechanisms for the palatability of sucrose and fat differ. In this study, administration of opioid receptor antagonists strongly suppressed the preference for Intralipid compared to sucrose in the two-bottle choice test (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Gas analysis was performed using an open‐circuit metabolic gas analysis system connected directly to a mass spectrometer (Model Arco2000; ArcoSystem, Chiba, Japan). The gas analysis system has been described in detail elsewhere . Briefly, each metabolic chamber had a 170‐cm 2 floor area and was 8 cm in height.…”
Section: Methodsmentioning
confidence: 99%
“…Food intake was measured for 10 days, and average intake per day was calculated. The respiratory gas analysis was performed with an Arco-2000 (Arco System), as described previously (25). Locomotor activity was measured with a 14-channel DAS system (Neuroscience).…”
Section: Mice-plin5mentioning
confidence: 99%